The Effect Of Different Depth Of Tuna Handline Fishing On Catches At KM Viona III Based In Cilacap Ocean Fishing Port, Central Java Province - Haris, Dendi; Sutono HS, Dian; Jamaludin, M; Perangin-angin, Robet; Tumpu, Mula (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2023)
Handline is a fishing gear that is selective about the catch and is a fishing gear that is passive or in the process of catching it there is a waiting period. The waiting period for the handline is the time when the bait is waiting for the fish to eat it. The depth of the hook on KM Viona III varies. The depth is divided into 2 groups between 45-60 m and 67.5-82.5 m. The purpose of this study was to determine whether or not there was an effect of differences in hook depth on catches by paired sample test t-test using SPSS 24. Based on the Wilcoxon test, non-parametric test hook depth test for total catches presented by SPSS 24 with asymp values .sig of 0.041. Because 0.041 < 0.05 means that there is a difference in catches based on the number of fish and it can be concluded that there is also an effect of hook depth on the number of catches, and the weight of the catch has a value of 0.023. Because the value is 0.023 <0.05, H0 is rejected and Ha is accepted, which means that there are differences in the weight of the catch at different depths and it can be concluded that there is also an effect of the depth of the hook on the weight of the catch. which was carried out at the Cilacap Ocean Fishing Port and participated in a 32-day arrest operation at KM Viona III.